Objects as pedagogical mediators. A proposal for the construction of an ecological design in the kindergarten - Cozzi , Federica; Pentini, Anna Aluffi (Revista Eletrônica de Educação, 2024)
Starting from the first days of life, the child is placed in the world as a subject intentionally interacting with individuals and with the environment that surrounds them, capable of generating meanings and knowledge through activities of playful and active learning. The kindergarten - the first broader social context that the child attends - is a privileged place for the development of project proposals aimed at the development of learning pathways to support the child in their growth and promote reflections on and participation in the topic of early childhood education at multiple levels. The article gives an account of the experience related to a personal research survey conducted at some public kindergartens (age 0-3) of the city of Rome in order to verify the replicability and effectiveness of a design methodology used in my work as a pedagogical coordinator. The methodology considers the use of elements present in the world of children and adults as mediators in the development of educational proposals that actively involve children, families and professionals that can generate a universe of shared meaning and promote a research-action perspective in educational services. This article also intends to highlight some design aspects of the curriculum (age 0-3) that could encourage the development of the kindergarten as a place that supports the child to be a protagonist of their growth pathways and the environment in which they live and contribute positively to their first experiences of citizenship.